Universality Theorems in Physics - Garbaliauskas, Antanas (Jaunųjų mokslininkų darbai, 2018)
The paper presents universality of some analytic functions, which is a very exceptional and useful property of zeta and L-functions. The property for the Riemann zeta-function was discovered by S. M. Voronin. Later, many mathematicians, such as S. M. Gonek, A. Reich, B. Bagchi, A. Laurinčikas, K. Matsumoto, R. Garunkštis, J. Steuding and others improved and generalized Voronin’s theorem. Physicists examine numerous models from different branches of physics (from classical mechanics to statistical physics) where this function plays an integral role.
Keywords: Rymann zeta-function; L-function; universality; applications in physics